Financial accounting - Tulsian, P. C. (Dorling Kindersley (India), 2006)
Texts on Financial Accounting have much in common; but differences run deep. The present text has been class-tested for more than twenty years. Rich in pedagogy and written in an easy-to-understand manner, this book adopts a fresh and novel approach to the study of accounting keeping in view the specific requirements of the students appearing in the B.Com. examination of the Indian universities and other professional examinations.